Organizational Citizenship Behavior for The Environment in University - Nawangsari, Lenny Christina; Sutawidjaya, Ahmad Hidayat; Suharko, Arief Bimantoro; Rudianto, Dudi (International Review of Management and Marketing, 2021)
The environmental concern has become an emerging topic in organization's human resource management strategy, especially in improving employee's environmental behavior at work. Currently, the social responsibility, especially the environmental responsibility has been of concern to scholars, organizations or governments. This study aims to analyze the effect of Green Transformational Leadership, Green Commitment and Organizational Culture on Job Satisfaction and its implications for Citizenship Behavior for the Environment (OCBE). The research method used is a qualitative method with the object of employee at university. Data analysis uses SEM (Structural Equation Model) with PLS (Partial Least Square) software. Research results prove there is an influence of Green Transformational Leadership, Green Commitment and Organizational Culture on Citizenship Behavior for the Environment (OCBE) through Job Satisfaction at University. Keywords: Green Transformational Leadership, Green Commitment, Organizational Culture, Job Satisfaction, Citizenship Behavior for the Environment JEL Classifications: L2, J2 DOI: https://doi.org/10.32479/irmm.10464